The Role of the Millennial Community in Achieving True Happiness - Anugraheni, Indri Wisdiarti; Pratama, Apriyadi Romadon; Hilal, Baleo (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: Being happy is a desire that anyone in this world has, including the millennial generation. The millennial generation has a positive influence on the progress of the nation, this is evidenced by the many young people who contribute to politics, economics and other fields. However, there are still many problems faced by the younger generation, ranging from problems of experience, strong mentality and good environment. This can be seen from the rise of suicides and mental illnesses as evidence of the implications of the modern world being a challenge for the younger generation. This research aims to find out how the concept of gratitude of the millennial community in achieving happiness to give birth to a generation of fighters. The research conducted is descriptive qualitative using literature studies and describing the results of previous research in order to obtain additional discussion for analysis of the discussion. The results of this study explain that gratitude is a very important teaching in religion, so that dhikr and worship are the implementation of gratitude to God in accordance with the Qur'an and hadith. As a servant of God, gratitude is not a compulsion but a necessity that is lived with a sense of happiness. Happiness is created and sought by doing good and being in a good community. Keywords: gratitude concept, millennial generation, happiness.